(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dharmawan IWE, Renyaan J, Nurdiansah D. 2022. Mangrove zonation, community structure and healthiness in Kei Islands, Maluku, Indonesia. Biodiversitas 23: 4918-4927. Forest structure and quality were studied in an archipelagic site in Indonesia which consists of estuarine and oceanic mangrove habitats. This study aimed to determine mangrove structure and estimate the spatial distribution of forest healthiness along the zones dominated by different genera. Forest zones were investigated using the Random Forest method utilizing a cloud-free Harmonized Sentinel-2A-Surface Reflectance image. Community structure measurement followed a stratified purposive sampling design along forest zonation. A spatial-based mangrove health index (MHI) model was applied to analyze forest healthiness distribution in each zone. Mangrove area was clearly classified into six genera-dominated zones such as Sonneratia, Rhizophora, Bruguiera, Ceriops, Xylocarpus and Lumnitzera from seaward to landward. The Rhizophora zone had the most extensive area proportion at approximately 68% of the total mangrove area. This study revealed that S. alba species dominated in the outmost zone at about 200% of IVI, while X. granatum and C. tagal were calculated in a larger IVI value in the more landward area. On the other hand, R. stylosa had a majority species composition in Rhizophora forest. According to spatial analysis of MHI, most zones had a majority area of excellent condition, emphasizing that the entire mangrove forest was pristine.